Dimensions of Public Policy in the Integration of Anti-Corruption Education in Civility Education Courses in Higher Education (Open Society Conference, 2023)
Corruption is one of the nation's problems and an extraordinary crime. The role of higher education makes an important contribution as a preventive measure in dealing with it. The issuance of the Minister of Research, Technology and Higher Education Regulation Number 33 of 2019 and several other government regulations is a public policy as a solution. The existence of policy actors, policy institutions and the policy environment is important for the integration of anti-corruption education in general compulsory courses. The research aims to analyze the substance of the anti-corruption education policy and the importance of the relationship between actors, institutions and the policy environment. The research uses normative juridical methods, literature studies and secondary data analysis, by examining the substance of government regulations and various relevant documents. The results of the study show that there are several government regulations which constitute anticorruption policies. Its integration into the Citizenship Education course is very strategic as an effort to prevent corrupt behavior. Government officials at the central and regional levels, Corruption Eradication Commission officials, officials from the Ministry of Education, Culture, Research and Technology, university leaders, lecturers teaching Citizenship Education courses, educational figures and activists, and other education stakeholders are policy actors. The Ministry of Education, Culture, Research and Technology, the Corruption Eradication Commission, universities and institutions outside the government are policy institutions. Societal expectations for reduced corruption are part of the policy environment. There are several policy substances in several government regulations that need to be perfected.